2022
DOI: 10.3390/life12101491
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Surface Changes Associated with Face Masks in Healthcare Personnel during COVID-19 Pandemic

Abstract: The aim of this study was to investigate ocular surface changes associated with face mask (FMs) use of healthcare personnel during the COVID-19 pandemic. We prospectively evaluated 200 eyes of 100 individuals during working hours and 40 eyes of 20 individuals during their rest days as a control group. Dry eye symptoms were assessed with the Ocular Surface Disease Index (OSDI) and McMonnies questionnaire. The clinical investigation included the best corrected visual acuity (BCVA), corneal fluorescein staining (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Dry eye diseases are the most common reported ocular complications of COVID-19 [ 51 ]. Krolo et al reported that face mask use was related to higher ocular surface disease index (OSDI) scores [ 44 ].…”
Section: Ocular Manifestations Of Covid-19mentioning
confidence: 99%
“…Dry eye diseases are the most common reported ocular complications of COVID-19 [ 51 ]. Krolo et al reported that face mask use was related to higher ocular surface disease index (OSDI) scores [ 44 ].…”
Section: Ocular Manifestations Of Covid-19mentioning
confidence: 99%